The genus Jeekelosoma Mauriès, 1985 – Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae) - Enghoff, Henrik; Reboleira, Ana Sofia P.S. (European Journal of Taxonomy, 2019)
Jeekelosoma Mauriès, 1985, is upgraded from subgenus status under Eviulisoma Silvestri, 1910 to full genus status. The type species, Jeekelosoma abadi (Mauriès, 1985) is redescribed based on topotypical material from a cave in Morocco. Jeekelosoma heptarachne sp. nov. and J. viginti sp. nov. are described from two further Moroccan caves.